Amyotrophic lateral sclerosis–specific quality of life–short form (ALSSQOL‐SF): A brief, reliable, and valid version of the ALSSQOL‐R. Issue 5 (19th October 2018) - Felgoise, Stephanie H.; Feinberg, Richard; Stephens, Helen E.; Barkhaus, Paul; Boylan, Kevin; Caress, James; Clawson, Lora L.; Elman, Lauren; Goutman, Stephen A.; Mccluskey, Leo; Russell, James; Tiryaki, Ezgi; et al.
ABSTRACT: Introduction : The Amyotrophic Lateral Sclerosis (ALS)‐Specific Quality of Life instrument and its revised version (ALSSQOL and ALSSQOL‐R) have strong psychometric properties, and have demonstrated research and clinical utility. In this study we aimed to develop a short form (ALSSQOL‐SF) suitable for limited clinic time and patient stamina. Methods : The ALSSQOL‐SF was created using Item Response Theory and confirmatory factor analysis on 389 patients. A cross‐validation sample of 162 patients assessed convergent, divergent, and construct validity of the ALSSQOL‐SF compared with psychosocial and physical functioning measures. Results : The ALSSQOL‐SF consisted of 20 items. Compared with the ALSSQOL‐R, optimal precision was retained, and completion time was reduced from 15–25 minutes to 2–4 minutes. Psychometric properties for the ALSSQOL‐SF and its subscales were strong. Discussion : The ALSSQOL‐SF is a disease‐specific global QOL instrument that has a short administration time suitable for clinical use, and can provide clinically useful, valid information about persons with ALS. Muscle Nerve 58 : 646–654, 2018